Prehistoric archaeology on the continental shelf : a global review - Flatman, Joseph C.; Flemming, Nicholas C.; Evans, Amanda M. (Springer New York, 2014)
Climate change, sea-level rise; these processes are a source of debate and concern in modern society due to their potential impacts on coastal populations. For archaeologists, climate change and sea-level rise have had a visible impact in the past, when thousands of prehistoric settlements on the continental shelf were inundated by the sea level rising as ice caps melted.   It has only been in the last forty years that we have begun to understand the ways in which climate change and sea-level rise have influenced the archaeological record of prehistoric societies. Archaeological sites on the world's continental shelves have previously been inaccessible to researchers, but advances in remote sensing and diving technologies have enabled exploration of these former terrestrial landscapes submerged by sea-level rise related to the last glacial maximum.   This edited volume presents multi-disciplinary case studies of prehistoric archaeological sites located on now-submerged portions of the continental shelf around the world. Each chapter represents an extension of the known prehistoric record beyond the modern shoreline. Case studies represent central themes of landscape change, climate change and societal development, using new technologies for mapping, monitoring, and managing these sites.